THE INFLUENCE OF PRACTICE FIELD EXPERIENCE (PPL) AND INTEREST IN BECOMING A TEACHER ON TEACHER READINESS IN STUDENTS OF MUHAMMADIYAH UNIVERSITY PROF. Dr. HAMKA - Aryani, Yenni; Purwana, Dedi; Marsofiyati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study aims to determine the effect of Field Experience Practice (PPL) and interest in becoming a teacher on readiness to become a teacher for students of the 2017 English Education Study Program, Muhammadiyah University Prof. Dr. Hamka. This research was conducted for 4 months starting from September 2021 to December 2021. The method used in this research is a survey method. The respondent selection technique used Proportional Stratified Random Sampling so that a sample of 147 respondents was obtained from students of the 2017 English Education Study Program, Universitas Muhammadiyah Prof. Dr. Hamka. Data collection was carried out through distributing questionnaires using a Likert scale and also using secondary data in the form of student PPL results. Based on the results of the research conducted, it was found that Field Experience Practice (PPL) had a positive and significant effect on Readiness to Become a Teacher. Interest in becoming a teacher has a positive and significant effect on readiness to become a teacher. In accordance with the research hypothesis.